2013
DOI: 10.1002/jts.21817
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐Related Correlates of Alcohol Use in Recently Deployed OEF/OIF Veterans

Abstract: The co-occurrence of posttraumatic stress disorder (PTSD) and alcohol use disorders (AUDs) is well documented. Little is known about the factors that contribute to alcohol use and the development of AUDs among military personnel following deployment. The primary aim of this study was to examine trauma-related correlates of alcohol use in recently deployed Operation Enduring Freedom/Operation Iraqi Freedom veterans. Members of the Rhode Island National Guard and Army Reserves (N = 238) completed an in-person, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
3
9
0
1
Order By: Relevance
“…From the reinforcement model perspective, smartphone use may serve to deal with the stress of intrusive memories and physiological/psychological reactivity in response to trauma reminders. Supporting our results are findings from the addiction literature; addictive behaviors such as alcohol use strongly relate to intrusion symptoms of PTSD (Capone, McGrath, Reddy, & Shea, 2013; Contractor, Presseau, et al, 2016). …”
Section: Discussionsupporting
confidence: 89%
“…From the reinforcement model perspective, smartphone use may serve to deal with the stress of intrusive memories and physiological/psychological reactivity in response to trauma reminders. Supporting our results are findings from the addiction literature; addictive behaviors such as alcohol use strongly relate to intrusion symptoms of PTSD (Capone, McGrath, Reddy, & Shea, 2013; Contractor, Presseau, et al, 2016). …”
Section: Discussionsupporting
confidence: 89%
“…And while income is strongly and negatively associated with household FI (5,9) , it is not the sole determinant and other factors relevant to management of household resources are also important. For example, research points to a connection between household FI and adult psychological well-being (10) , including psychosocial problems like post-traumatic stress disorder, depression, binge drinking and substance use disorders that may be associated with military service (11)(12)(13)(14)(15)(16)(17)(18)(19) . The transition from military to civilian life often presents unique barriers to financial security, which may amplify the risk of experiencing FI.…”
mentioning
confidence: 99%
“…Contrary to expectations, there were no significant differences regarding symptoms of PTSD, depression, and anxiety by the frequency of current alcohol use. While some studies have found no relationship between alcohol use and PTSD symptoms (Gurdil, 2007 ) and even a lower incidence of alcohol use among patients with PTSD (Dalbudak, 2008 ), the association between PTSD and alcohol consumption is the more common finding (Capone, McGrath, Reddy, & Shea, 2013 ; Fetzner, Abrams, & Asmudson, 2013 ). It is assumed that religion is a predominant factor for Turkish veterans for not drinking or reporting themselves as not drinking since it is forbidden to drink alcohol in Islam.…”
Section: Discussionmentioning
confidence: 99%